Effects of Transcription-Dependent Physical Perturbations on the Chromosome Dynamics in Living Cells - Ku, Hyeyeong; Park, Gunhee; Goo, Jiyoung; Lee, Jeongmin; Park, Tae Lim; Shim, Hwanyong; Kim, Jeong Hee; Cho, Won-Ki; Jeong, Cherlhyun (Frontiers in Cell and Developmental Biology, 2022)
Recent studies with single-particle tracking in live cells have revealed that chromatin dynamics is directly affected by transcription. However, how transcription alters the chromatin movements followed by changes in physical properties of chromatin has not been elucidated. Here, we measured diffusion characteristics of chromatin by targeting telomeric DNA repeats with CRISPR-labeling. We found that transcription inhibitors that directly block transcription factors globally increased the movements of chromatin, while the other inhibitor that blocks transcription by DNA intercalating showed an opposite effect. We hypothesized that the increased mobility of chromatin by transcription inhibition and the decreased chromatin movement by a DNA intercalating inhibitor are due to alteration in chromatin rigidity. We also tested how a volume confinement of nuclear space affects chromatin movements. We observed decreased chromatin movements under an osmotic pressure and with overexpressed chromatin architectural proteins that compact chromatin.